Perancangan dan Pembaharuan Dokumen Sertifikasi ISO 9001:2015 pada PT. X - Feybiola Utomo; Jani Rahardjo (Jurnal Titra, 2022)
PT. X has received ISO 9001:2015 certification, but in its application there are still some deficiencies of the required documents. The existing certifications require renewal of certification in the future. In order to prepare companies to confront the internal and external audit processes to renewing certification, the companies needs to complete the ISO 9001:2015 requirements documents. The company will be assisted to making the documents that do not yet exist and updating documents that need to be revised according to the current state of the company and the requirements of ISO 9001:2015. The first results of the initial gap analysis shows that PT. X has a fairly high gap. The average percentage of document fulfillment in the initial gap analysis is 50%. After making and updating documents, the average percentage of document fulfillment has increased, which is 100%. The increase of the percentage of document fulfillment that owned by the company was 50%.